Ethics, Empirics and Esthetics: The Visibility of Nursing and the Sustainability of Human Health in a Technological World - Locsin, Rozzano C. (Journal of Research in Nursing-Midwifery and Health Sciences, 2017)
Ethics, empirics, and esthetics seem to address the essential nature of nursing knowledge within the human health experience. Reality, truth and existence are the empirical elements of the human experience. Reflexivity conveyed in esthetic ways illuminates the nature and context of humanness. Art as experience uncovers meanings and significance of lived situations. Ethical values are dictated by philosophical, theoretical, social and cultural perspectives. Conflicts primarily address the need for ethical solutions stemming from perceived versions of truths. The conditions that engender truthful solutions on questions about health and well-being are highly likely situational dilemmas. Through art as representation of what is real and true, labeled and displayed for sensory appreciation, the ethical and empirical ways of appreciating human health and well-being become foundational realities for nursing practice, sustainable in esthetic ways as integral to human health and well-being.